The Influence of Work Environment Factors on the Ocular Surface in a One-Year Follow-Up Prospective Clinical Study - Edyta Chlasta-Twardzik; Aleksandra Górecka-Nitoń; Anna Nowińska; Edward Wylęgała (Diagnostics, 2021)
The purpose of this study was to assess the effect of environmental working conditions on the symptoms and signs of dry eye disease and to examine whether and how those conditions impact the ocular surface. Methods: This single-center, prospective clinical study with a 1-year follow-up included 150 patients. The following parameters were evaluated: non-invasive keratograph break-up time (NIKBUT), tear meniscus height (TMH), and conjunctival and limbal hyperemia. We also performed staining of the surface of the eye for simulated fluorescein images, Schirmer’s test I, assessment of Meibomian gland dysfunction (MGD), and an Ocular Surface Disease Index (OSDI) questionnaire. Results: In the OW (office workers) group, in people working >4 h at the computer, the NIKBUT before work and the Schirmer test results were statistically significantly lower than in people working <4 h. The conjunctival hyperemia result before work was statistically significantly higher for people working >4 h at a computer in both groups and after work in the MW (medical workers) group. Low relative air humidity in the building and air-conditioned rooms negatively affects the tear film, causing the symptoms of dry eye disease. At the 1-year follow-up, there was a statistically significant reduction in conjunctival and limbal hyperemia in the OW group as well as a statistically significant reduction in TMH at the first examination before and after work, and in the second examination after 1 year in both groups. Conclusions: Environmental factors such as reduced relative air humidity, increased air temperature, and decreased illumination have a negative impact on the ocular surface.